Revisiting local history in the Philippines - Mojares, Resil B. (Journal of Philippine local history and heritage, 2015)
The paper looks back to the "movement" to promote local historical studies that spanned the years from the late 1960s, and inquiries into the reasons for the movement's emergence. The paper argues for the continuing relevance of this movement today and the need to rejuvenate it in terms of fresh inituatives in archive building, support for local centers of historical research, networking of local historical societies, and critical assessments of the state of the field.